Synergizing water desalination and hydrogen production using solar stills with novel sensible heat storage and an alkaline electrolyzer - Habib Ben Bacha; Abanob Joseph; A.S. Abdullah; Swellam W. Sharshir (Case Studies in Thermal Engineering)
This study tested a cogeneration (desalination/hydrogen production) system with natural and black sand as sensible heat storage, considering the thermal efficiencies, environmental impact, water quality, cost aspects, and hydrogen generation rate. The black sand-modified distiller attained the highest water production of 4645 mL, more than the conventional distiller by 1595 mL. It also offered better energy and exergy efficiencies of 45.26 % and 3.72 %, respectively, compared to 32.10 % and 2.19 % for the conventional one. Both modified distillers showed impressive improvements in water quality by significant reductions in total dissolved solids (TDS) from 29,300 mg/L to 60–61 mg/L. Moreover, the black sand-modified still reduced chemical oxygen demand (COD) to 135 mg/L. The production cost was minimized by using black sand to 0.0111$/L, higher than one-fifth in the case of the lab-based distiller. Regarding hydrogen production, the highest rate was obtained using distilled water from a lab-based distiller of 0.742 gH₂/hr with an energy efficiency of 11.00 %; however, it was not much higher than the case of black sand-modified still (0.736 gH₂/hr production rate and 10.91 % efficiency). Moreover, the black sand-modified still showed the highest annual exergy output of 70.4 kWh/year, with a significant yearly decarbonization of 1.69 ton-CO2.